Women and Natural Catastrophe: Managing Risks and Chances for Family Endurance - Haryanti, Nana (Universitas Negeri Semarang, 2020)
Increasing natural degradation has started affecting society particularly women. Conversation links between women and nature is ended up with the fact that women who are mostly suffering from any natural degradations. Natural degradation will lead women to poverty as they have no choices and opportunities to move to satisfactory condition of wealth. In very limited means and infrastructure owned, women take any responsibilities fulfilling family and society needs. In order to avoid possible family shortage, women living in the fishing village work harvesting water hyacinth, an invasive aquatic plant which has negative impact on ecosystem, and gain economic benefits from processing water hyacinth, whilst developing many other domestic strategies for family survival. Ã‚Â Ã‚Â